Hepatocellular carcinoma targeted therapy and multidisciplinary care - McMasters, Kelly M.; Vauthey, Jean-Nicolas (Humana Springer [distributor], 2011)
"Hepatocellular Carcinoma: Targeted Therapy" provides a detailed repository of the latest information regarding HCC epidemiology, diagnosis, imaging, pathology, staging, and treatment options. This volume also provides an up-to-date guide for treatment that explores not only traditional treatments, but newer investigational treatment options including, surgical resection, liver transplantation, ablation (radiofrequency, microwave), percutaneous ethanol or acetic acid injection, transarterial chemoembolization (TACE), intra-arterial radiation therapy, and systemic chemotherapy."